2018
DOI: 10.1002/cpdd.576
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability, Pharmacokinetic and Pharmacodynamic Evaluations Following Single Oral Doses of GSK2330672 in Healthy Japanese Volunteers

Abstract: GSK2330672 is an inhibitor of the ileal bile acid transporter, designed to have minimal systemic exposure, and is under development as a potential therapeutic for pruritus associated with primary biliary cholangitis and other cholestatic liver diseases. A phase 1, double-blind, placebo-controlled, 4-period crossover study was conducted to evaluate the safety, tolerability, and pharmacokinetic/pharmacodynamic characteristics of GSK2330672 in healthy Japanese participants. Sixteen healthy male participants recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…All three IBAT inhibitors showed similar adverse events: dose-dependent diarrhea (up to 50, 100, and 83% with A4250, SHP626, and GSK2330672, respectively) and abdominal pain (up to 33, 78, and 17% with A4250, SHP626, and GSK2330672, respectively) ( Graffner et al, 2016 ; Ino et al, 2018 ; Tiessen et al, 2018 ).…”
Section: Phase I Clinical Trials With Ibat Inhibitorsmentioning
confidence: 87%
See 1 more Smart Citation
“…All three IBAT inhibitors showed similar adverse events: dose-dependent diarrhea (up to 50, 100, and 83% with A4250, SHP626, and GSK2330672, respectively) and abdominal pain (up to 33, 78, and 17% with A4250, SHP626, and GSK2330672, respectively) ( Graffner et al, 2016 ; Ino et al, 2018 ; Tiessen et al, 2018 ).…”
Section: Phase I Clinical Trials With Ibat Inhibitorsmentioning
confidence: 87%
“…The third trial evaluated the IBAT inhibitor GSK2330672 in a 4-period crossover study in 16 Japanese subjects with single oral doses of GSK2330672 (10–180 mg) or placebo in each period. A dose-dependent tendency for total serum BAs to reduce and for serum C4 to increase was observed ( Ino et al, 2018 ).…”
Section: Phase I Clinical Trials With Ibat Inhibitorsmentioning
confidence: 99%
“…In this matter, a later study in healthy Japanese volunteers investigated the safety and tolerability of GSK2330672 versus placebo. No serious adverse events were present and the main side effects was diarrhea [74]. Another, but larger placebo-controlled trial found that GSK2330672 was not significantly different versus placebo [75].…”
Section: Asbt Inhibitorsmentioning
confidence: 94%
“…In this matter, a later study in healthy Japanese volunteers investigated the safety and tolerability of GSK2330672 versus a placebo. No serious adverse events were present and the main side effect was diarrhea [ 77 ]. Another, but larger, placebo-controlled trial found that GSK2330672 was not significantly different versus placebo [ 78 ].…”
Section: Therapeutic Optionsmentioning
confidence: 99%